Investigation of the Local thermal Non-Equilibrium (LTNE) effects on magneto-natural convection of nano-encapsulated PCMs in an elliptical non-Darcian porous annulus - Tayebi, Tahar; Öztop, Hakan Fehmi (Elsevier Science Inc, 2025)
Energy efficiency is primarily reliant on energy storage equipment, making it an essential technology in the current era. Thermal management, achieving a consistent temperature and adequate heat transfer through cooling, is crucial in these systems. This paper focuses on a careful analysis of the effects of Local Thermal NonEquilibria (LTNE) on heat transfer and fluid flow by free convection in a non-Darcy porous medium saturated with a water-based suspension of Nano-Encapsulated Phase Change Materials (NEPCMs) enclosed within an elliptical annular space. This configuration is also subject to a horizontal magnetic field as a means of external control of the thermal process. The inner cylinder is kept at a higher temperature while the outer cylinder is kept at a lower temperature, resulting in convective circulation and allowing the encapsulated particles to absorb and release heat. The Darcy-Brinkman Forchheimer updated model is used to address the Navier-Stokes equations in their dimensionless form, which are then solved numerically using the finite volume method. The local thermal non-equilibrium in the porous medium, including the dimensionless interface heat transfer coefficient between the solid matrix and NEPCMS suspension (H) and thermal conductivity ratio (gamma), has been analyzed for the strength of convective flow and heat transfer for the solid and fluid phases for various Stefan number (Ste) and core fusion temperature (theta f) values. The investigation showed the importance of taking into account LTNE when improving heat transfer by natural convection process using encapsulated in nanoparticles materials (NEPCMs). The convective flow power is found to augment with H and diminish with gamma. Furthermore, Nus_avg increases by 95.05% as H varies from 1 to 1000, and by about 157.5% as gamma varies from 0.1 to 100. Meanwhile, Nuf_avg increases by 17.18% with gamma but decreases by 2.2% with H.
Keywords: MHD Natural convection; Nano-Encapsulated Phase Change Materials; (NEPCMs); Porous medium; Local Thermal Non-Equilibrium (LTNE); Elliptical annulus